Case Report: Acute myocarditis and cerebral infarction following Bothrops lanceolatus envenomation in Martinique: a case series - Florentin, Jonathan; Farid, Karim; Kallel, Hatem; Neviere, Remi; Resiere, Dabor (Frontiers in Cardiovascular Medicine, 2024)
Bothrops lanceolatus (Bl), a snake endemic to Martinique, is responsible for numerous envenomations annually, leading to severe complications such as thrombosis, necrosis, and hemorrhage. This case series investigates the link between Bothrops lanceolatus envenomation and acute myocarditis, utilizing cardiac magnetic resonance imaging (MRI) to enhance management strategies. In both cases, cardiac MRI confirmed myocarditis with edema, and subsequent cerebral MRI revealed bilateral infarcts. Elevated troponin levels further supported the myocarditis diagnosis. Multiple doses of Bothrofav® antivenom facilitated recovery without clinical after effects.These cases represent the first documented instances of myocarditis due to Bl envenomation confirmed via cardiac MRI. Prompt administration of antivenom and the use of advanced imaging techniques were crucial in achieving favorable outcomes.